Evaluating international impacts of China-specific shocks in an input-output framework - Heli Simola (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
The slowing in China's massive economy has wide implications. China plays an essential role in international production chains, so disturbances can spill over to other economies in the global production network. We evaluate the international transmission and impact of various China-specific shocks with an input-output framework applied to the World Input-Output Database (WIOD). We consider shocks to Chinese final demand at the aggregate level, bilateral import tariffs between the US and China and sector-specific shocks to Chinese final demand and supply. Our results suggest that aggregate level shocks, as well as certain sector-specific shocks originating in China, may have large impacts elsewhere. Transmission of shocks through the global production network, however, is mitigated by the relatively low import-intensity of Chinese production.
URN:NBN:fi:bof-201909091444
Keywords: C67; F14; F43; 330; Chinese economy; shock transmission; input-output; international production network